Brokered Careers: The Role of Search Firms in Managerial Career Mobility. (January 2023) - Bidwell, Matthew; Choi, Kira; Fernandez-Mateo, Isabel
The authors explore how career paths are shaped by the involvement of search firms in hiring. Drawing on theories of market intermediation, they argue that search firms constrain horizontal moves across functions and industries by favoring workers from within the same function and industry as the role being filled. Using survey data on 1, 342 job moves undertaken by 816 MBA alumni, the authors find that individuals who move jobs through a search firm experience lower horizontal mobility than those who move through other means. Findings also suggest that these results are not driven by firms' decisions to use a search firm to fill the job. Supplementary analyses show no evidence that the job matches that are formed using search firms result in a better fit between workers and employers. Overall, the findings point to the significant institutional role search firms play in managerial careers.